Evaluating the effectiveness of learning design with mixed reality (MR) in higher education - Tang, Y. M.; Au, K. M.; Lau, H. C. W.; Ho, G. T. S.; Wu, C. H. (Virtual reality : the journal of the Virtual Reality Society, 2020)
Virtual reality (VR) is rapidly developed and bringing advancement in various related technologies through the virtual world. It has high potential and plays an important role in education and training fields. Mixed reality (MR) is a type of hybrid system that involves both physical and virtual elements. While VR/MR has proved to be an effective way to improve the learning attitude and effectiveness for secondary students, however, not much work has been conducted on university students to compare the MR experience and traditional teaching approaches in learning design subjects. In this project, we investigated the effectiveness of students in learning design subjects with the support of MR. The effectiveness was measured based on their creativity and systematic approaches in design. Pretests and posttests were conducted to measure the learning effects. We also compared the learning effectiveness of a student’s study with the MR and traditional teaching materials. Nonparametric analyses were conducted to investigate whether the improvements were significant. Experimental results showed that after studying with the support of the MR technology, the students’ abilities in geometric analysis (mean difference = 4.36, p < 0.01) and creativity (mean difference = 1.59, p < 0.05) were significantly improved. The students’ ability in model visualization was also significantly better than the control group (mean difference = 3.08, p < 0.05). It indicated that the results were positive by using the MR to support their study. The MR was also better than using traditional teaching notes in various measured effects.